KOEFISIEN RESPON LABA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ni Putu Erviani Astari (Journal Research of Accounting, 2023)
Profit is one of the information used in investment decisions. Investors can make the right investment decisions if they use high-quality earnings information. This study analyzes the earnings response coefficients of companies listed on the Indonesia Stock Exchange from 2017 to 2021. The sample in this study was 272 companies and determined by the purposive sampling method. The sample was analyzed using earning response coefficients with abnormal return accumulation as the dependent variable and abnormal earnings as the independent variable. Tests are carried out every year from 2017 to 2021 using statistical tests. The test results show a decrease in the earnings response coefficient for companies listed on the Indonesia Stock Exchange. Thus, investors cannot only use earnings information to make decisions. They must combine earnings information and other information (quantitative or qualitative) to avoid making wrong investment decisions.